A New approach to Helping the hard-to-place Unemployed: The promise of developing new knowledge in an interactive and collaborative process. Issue 4 (December 2017) - Andersen, Niklas A.; Caswell, Dorte; Larsen, Flemming
The reforms of the social and employment services that have swept across most of the developed world since the 1990s have enormously expanded the groups of citizens receiving active employment measures. Nevertheless, up until now, most countries have only seen limited results from enhancing the labour market participation of the most vulnerable groups. We argue that the goal of including a greater share of the harder-to-place unemployed in the labour market is not likely to be achieved through the tried and tested ways of developing knowledge, policy and practice. Rather, we propose a different approach to generating and exchanging the necessary knowledge for developing active employment policy and practice. As an alternative to the evidence-based knowledge paradigm, we set up a model for knowledge production that is made through co-operation between practice and research. This model investigates the potential for integrated services and for co-production by acknowledging the importance of the experiences of frontline professionals and clients in developing employment services.